Identifikasi Strategi Cina Dalam Upayanya Menguasai Doklam 2004-2018 - Putra Purohita, I Gede Pradnya; Priadarsini, Ni Wayan Rainy; Suwecawangsa, Adi P. (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT This research to identify what strategies the China use in their efforts to claim the Doklam region. This identification is based on the characteristics that contained in every China action and behavior related to the Doklam conflict. The issue of territorial conflict in the Doklam region is an old issue since1960s has heated up again in 2017 when China was exposed doing road construction in Doklam. This was criticized by Buthan and India who considered China to have committed a violation by carrying out road construction in Doklam area that was still in a disputed status or quo status. This analyzed with the concept of territorial conflict to explain what benefits can be obtained from the ownership of Doklam and the concept of salami slicing strategies to describe what components are in accordance with China actions and behavior can be used to identify the strategies that China uses. Keywords : China, Doklam, Salami Slicing, India, Buthan